Assessment of Children with Autism Spectrum Disorder and Post-Assessment Meeting with Parents: Some Issues of Planning and Professional Attitude - Terziev, D.; Manolova, H.; Staykova, S.; Hristova, M. (Journal of Intellectual Disability - Diagnosis and Treatment, 2018)
The authors, child psychiatrists and clinical psychologists, conducting team assessment of children with developmental disabilities (including autism spectrum disorder) for more than two decades, present some important in their view issues and recommendations concerning planning and proceeding of assessment and post-assessment meetings with parents. It is essential to ensure not only an accurate assessment protocol and diagnosis, but also to “attune” to parents in order to facilitate their understanding and more positive use of assessment outcome results. Parents need further support to “survive” psychically the post - assessment period and to provide for adequate interventions for their child.